Traditional Chinese medicine for acute coronary syndrome: A meta-analysis of clinical manifestations and objective indicators. Issue 33 (20th August 2021) - Liao, Jiangquan; Li, Tao; Hua, Yingying; Shao, Mingjing; Wang, Yan; Wang, Zhe; Wei, Kangkang; Chang, Jiangmeng; Zhang, Xiaoqiong; Chen, Ming; Li, Xianlun; Du, Jinhang
Abstract: Background: Modern clinical trials and experimental researches of traditional Chinese medicine (TCM) have been conducted for decades and provided support for the prevention and treatment of acute coronary syndrome (ACS). However the level of evidence and the proper application of TCM were still barely satisfactory. Methods: In this study, we divided ACS into 3 different stages, including unstable angina, acute myocardial infarction, and post myocardial infarction. Then we systematically reviewed and meta-analyzed the existing randomized controlled trials on both clinical manifestations and objective indicators, in these 3 aspects. Results: The results indicate that TCM can both improve the clinical manifestations and ameliorate the objective parameters in different courses of ACS, including C-reactive protein in unstable angina, left ventricular ejection fraction in acute myocardial infarction and post myocardial infarction. And the incidence of short-term cardiovascular events are lower in TCM intervention group. Some of the improvements lead to potential long-term benefits. Conclusion: TCM treatment is beneficial to different courses of ACS. To acquire more solid and comprehensive evidence of TCM in treating ACS, more rigorously designed randomized controlled trials with longer follow-up duration are warranted.